(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
the research was carried out in the field of the REEL technical engineering agrocluster in the Orta Chirchik district. For this, cotton plants with a distance of 100x100 meters were selected. First, the first bolls opened on the cotton after defoliation were harvested, then bolls weighing about 1 kg, ripened for 3 days, 6 days, 9 days and 12 days, were harvested. The peeled bolls were separated from the fiber by hand. The physical and mechanical properties of the fiber were determined.